Comparative antiradical activity and molecular Docking/Dynamics analysis of octopamine and norepinephrine: the role of OH groups. (February 2020) - Dimić, Dušan; Milanović, Žiko; Jovanović, Goran; Sretenović, Dragana; Milenković, Dejan; Marković, Zoran; Dimitrić Marković, Jasmina
Graphical abstract: Highlights: A suitable level of theory for the description of octopamine is B3LYP-D3BJ/6−311 G(d, p). Additional OH group influences the scavenging reaction rates and thermodynamics. The dominant mechanism of DPPH and ABTS scavenging is SPLET. Additional bonds are present in β1/β2- adrenergic receptors-norepinephrine complex. Protein complexes have similar flexibility, interatomic distances and compactness. Abstract: Octopamine is a neurotransmitter in invertebrates and a phenol analog of norepinephrine. The crystallographic and spectral (UV–visUV, and NMR) characteristics of octopamine were investigated experimentally and theoretically by applying appropriate level of theory, B3LYP-D3BJ/6-311++G(d, p), which reproduced well the experimental bond lengths and angles. The intramolecular interactions governing the stability of conformers were described by NBO and QTAIM analyses. The antiradical potencies of octopamine and norepinephrine towards DPPH and ABTS + were examined with special emphasis on the preferred mechanism and effect of catechol moiety. Several techniques were used to distinguish Hydrogen Atom Transfer (HAT) and Proton Coupled Electron Transfer (PCET) mechanisms for reaction with DPPH . The calculated rate constants of the reactions with both radicals showed that Sequential Proton Loss Electron Transfer (SPLET) mechanism was dominant both thermodynamically and kinetically, with values of thermodynamic functions and rate constants clearly proving the importance of the second hydroxyl group in structure. The Molecular Docking and afterward Molecular Dynamics calculations of formed complexes between octopamine/norepinephrine with β1- and β2- adrenergic receptors examined in details the interactions that lead to the formation of stable complexes. The number of strong interactions of amino acids with norepinephrine was higher, but the absence of hydroxyl group in octopamine did not lead to a significant change in the type of interactions and stability. The formed complexes showed higher flexibility of amino acids, similar compactness of structure as proteins and increased interatomic distances of the backbone when compared to pure proteins.